PENGARUH PENGGUNAAN MEDIA KONVENSIONAL DAN NEW MEDIA TERHADAP TINGKAT SOSIALISASI POLITIK MAHASISWA FISIP UNDIP (STUDI KASUS MAHASISWA STRATA SATU) - Ramadhan Triwijanarko; Susilo Utomo; Wiwik Widayati (Journal of Politic and Government Studies, 2013)
AbstractPolitical socialization is a process of how the political system introduced to someone,and how to determine the person's response and reaction to the political phenomenon. One of theagents of political socialization is the mass media. In the modern era of mass media has beendivided into two camps, the conventional media and new media. Widespread development oftechnology and inexpensive price make the new media accessible to many people. Whileconventional media slowly began to incontestably with the new media. Students are actively inuse at the age of new media, how the use of conventional media and new media by students ofFaculty of Social undip and what influences the level of political socialization of studentsKeywords: new media, conventional media, political socialization